Health Education on Clean and Healthy Living Behavior through Proper Handwashing among Elementary School Students at SD Negeri Serdang Kulon 1 - Dwi Nurmawaty; Muniroh Muniroh; Budi Indrawan; Gadiza Azahra; Marsha Navita Putri (Abdimas Paspama, 2025)
Proper handwashing is a crucial component of clean and healthy living behavior, especially for school-age children who are highly vulnerable to various diseases due to their daily interactions in the school environment. This community service activity aimed to educate elementary school students on the importance of hand hygiene and to teach them the correct handwashing techniques using both soap and hand sanitizer. The method involved direct counseling sessions, visual aids through leaflets and posters, and interactive demonstrations. The evaluation included pre- and post-activity questionnaires and practical demonstrations. Although there was a positive change in students’ knowledge, the outcome did not fully meet the expected target. Several challenges, such as limited time, classroom distractions, and the complexity of the questionnaire for young learners, hindered optimal results. Nonetheless, the activity succeeded in raising awareness about proper hand hygiene and laid the groundwork for future improvements in health education among young students